Campus ecology: assessing the performance and management of green infrastructure at Kansas State University - Freelove, Lukas (My University, 2025)
Green infrastructure is essential for creating healthy, sustainable spaces by integrating natural systems into urban environments. It enhances human well-being and ecological resilience while providing key ecosystem services like stormwater management. As green infrastructure projects become more popular and, in some cases, mandatory, these systems must be well-designed, properly implemented, and adequately maintained. Unfortunately, many projects suffer from issues stemming from poor design, faulty implementation, or inadequate maintenance. At Kansas State University, for instance, several green infrastructure projects require more attention. This issue is not unique to KSU; numerous other projects across various locations also need improvements in design and management. This research focuses on how increasing biodiversity and effective management strategies of green infrastructure can benefit its performance and the crews responsible for its upkeep. The study will explore these systems' planting strategies, design, performance, and current management practices. The research will culminate in a proposed design for green infrastructure and strategies for improved management.
Keywords: Maintenance; Green infrastructure; Green infrastructure management; Biodiversity; Campus design